Ocular involvement in newly diagnosed pediatric leukemia: A systematic review and meta‐analysis - Kristina Nazzicone; Rachel Kim; Alexa Fine; Aidan Pucchio; Laura Wheaton; Christine Law (Pediatric Investigation)
ABSTRACT Importance Ocular involvement in pediatric leukemia is often under‐recognized, especially in asymptomatic cases. Prevalence estimates of childhood leukemic ophthalmopathy range from 0.32% to 71%, depending on the study design and population. Objective To determine the prevalence and describe the nature of ocular involvement in newly diagnosed pediatric leukemia through systematic review and meta‐analysis. Methods A comprehensive search of MEDLINE, Embase, Cochrane, and Web of Science databases was conducted up to July 2024. Studies reporting on ocular involvement at diagnosis in children aged 18 years or younger with leukemia were included. Cases of relapsed disease were excluded as were those receiving concurrent treatment. A random effects meta‐analysis using an inverse‐variance restricted maximum likelihood approach was performed for prevalence estimates. Results Fourteen studies involving 2989 pediatric leukemia patients were included. The overall pooled prevalence of ocular involvement at diagnosis was 20.32% (95%CI = 9.88%–33.08%). The prevalence of asymptomatic ocular involvement was higher at 23.90% (95%CI = 10.27%–40.63%) compared to 14.75% (95%CI = 0.00%–45.31%) for symptomatic involvement alone. High heterogeneity (I2 = 97.7%) was observed across studies, likely driven by differences in study design and populations. Interpretation Ocular involvement in newly diagnosed pediatric leukemia is more common than previously understood, particularly for asymptomatic cases. Current practices of selective ophthalmic assessment may miss a number of early‐stage ocular manifestations, emphasizing the need for all newly diagnosed patients to be screened for ophthalmic involvement at the time of diagnosis.